Effect of four-week Kinesio-taping on Tibialis anterior muscle activation and functional mobility in stroke Patients with foot drop: A Pre-Post intervention study (International Journal of Physiotherapy, 2024)
Background: Stroke is the second leading cause of mortality worldwide after coronary artery disease and the most common cause of chronic adult disability. A primary impairment following stroke is weakness or paresis, affecting 80 to 90% of patients. Foot drop, caused by weakness of the tibialis anterior muscle and spasticity of the plantar flexors, impairs the ability to raise the foot during the swing phase of walking. This leads to decreased mobility, disrupted walking patterns, and significant limitations in daily activities, potentially resulting in long-term disability.Methods: A total of 20 post-stroke patients with foot drop were included in the study. Baseline data were collected using RMS and TUG. The patients were given Kinesiological taping to TA and HMS, keeping in mind the PNF pattern, conventional physiotherapy, and conventional physiotherapy alone.Results: Compared to baseline data in group-1, there was a significant change in TUG score but no significant change in RMS, while in PNF kinesiological taping to TA and HMS group-2 had a significant effect on TA muscle activation (p